ANALISIS PELAKSANAAN GADAI TANAH PERTANIAN BERDASARKAN UNDANG-UNDANG NO. 56 PRP TAHUN 1960 TENTANG PENETAPAN LUAS TANAH PERTANIAN ( Studi Kasus di Kenagarian Simpang Tonang, Kecamatan Dua Koto, Pasaman ) - Ihdi Aini (Institut agama islam negeri Padangsidimpuan, 2020)
The implementation of the pawn in the Simpang Tonang Regency, Pasaman District is based on traditional law that has been in effect for a long time. This study aims to deteemine the suitability of implementation of the pawn that is applied in the village of Simpang Tonang with the implementation of the pawning regulated under Law No. 56 Prp 1960 concerning Determination of Agricultural Land Area. In Article 7 of the Law it is stated that the use of pawned land may only be for a period of 7 years. If the pawning has been going on for 7 years, the pawned land must be returned to the owner without ransom. The type of research used is field research with data collection techniques through observation and interviews with pawners, pawn recipients, and community leaders of Simpang Tonang Village. The data obtained were analyzed using inductive, deductive, and comparative methods. From the results of the analysis conducted, it is known that the implementation of the pawn is not in accordance with the provisions of Law No. 56/Prp/1960. The implementation of the pawn is more likely to benefit the pawner and it is colored by extortion of the pawner to the point that the desired goal of Law No. 56/Prp/1960, wich provides protection to the people of the economically weak group and to avoid the practise of mortgage lenders.